Manual Budgeting and Forecasting and Its Disadvantages - Linda Nguyen; John Lee (Research Parks Publishers, 2021)
A financial forecast is a budgeting tool that shows estimated statistics based on past, present, and future financial conditions. Without a prediction, the annual budgeting process is incomplete. A strong forecast allows for improved financial decision-making and the delivery of important community services. The fundamental difference between a budget and a forecast is that a budget outlines a company's plan for achieving its goals, but a forecast outlines the company's actual results expectations, usually in a much more concise manner. In actuality, the prediction is the more important of the two tools because it provides a short-term snapshot of a company's current situation. Monthly, quarterly, or weekly rolling forecasts are used to help you plan for a specific time period that isn't covered by the yearly budget, such as the next five quarters. As a result, most rolling predictions will forecast the next 12 months or more, rather than just the fiscal year's end. Once a fiscal month or quarter has been actualized, your prediction simply